Effects of Model Resolution, Physics, and Coupling on Southern Hemisphere Storm Tracks in CESM1.3. Issue 21 (7th November 2019) - Meehl, Gerald A.; Yang, Dongxia; Arblaster, Julie M.; Bates, Susan C.; Rosenbloom, Nan; Neale, Richard; Bacmeister, Julio; Lauritzen, Peter H.; Bryan, Frank; Small, Justin; Truesdale, John; Hannay, Cecile; et al.
Abstract: Two high‐resolution versions of a Coupled Earth System Model (CESM1.3: 0.25° atmosphere, 1° ocean; CESM1.1: 0.25° atmosphere, 0.1° ocean) are compared to the standard resolution CESM1.1 and CESM1.3 (1° atmosphere, 1° ocean). The CESM1.3 versions are documented, and the consequences of model resolution, air‐sea coupling, and physics in the atmospheric models are studied with regard to storm tracks in the Southern Hemisphere as represented by 850‐hPa eddy kinetic energy. Increasing the resolution from 1° to 0.25° in the atmosphere (same physics) coupled to the 1° ocean intensifies the strength of the storm tracks closer to observations. The 0.25° atmosphere with the older CESM1.1 physics coupled to the 0.1° ocean has fewer low clouds, warmer Southern Ocean sea surface temperatures, a weaker meridional temperature gradient, and a degraded storm track simulation compared to the 0.25° atmosphere with CESM1.3 physics coupled to the 1° ocean. Therefore, deficient physics in the atmospheric model can negate the gains attained by higher resolution in atmosphere and ocean. Key Points: Progression from CESM1.1 to CESM1.3 is documented with improved physics and better simulation of low clouds in CESM1.3 compared to CESM1.1 Southern Hemisphere storm tracks intensify in closer agreement with observations with higher resolution in the atmosphere except in the model version with older physics Deficient physics in the atmospheric model can negate the gains attained by higher resolution in atmosphere and ocean Plain Language Summary: Southern Hemisphere storm tracks intensify in closer agreement with observations with higher resolution in the atmosphere except in the model version with older physics, such that deficient physics in the atmospheric model, which produce less low clouds, a reduced meridional sea surface temperature gradient, and weaker storms in the Southern Hemisphere, can negate the gains attained by higher resolution in atmosphere and ocean.